Dot-Dot-Dot: A Feminist Critical Poetic Inquiry of Silence in Teacher Candidates’ Responses to Teaching Sexual Assault Narratives - Moore, Amber (Journal of the Canadian Association for Curriculum Studies, 2022)
This project emerges from a larger feminist study where 23 teacher candidate participants took up reading a trauma text set of sexual assault literature and responded to pedagogy for teaching such narratives with adolescents in Canadian K-12 public schools. This critical feminist poetic inquiry (Faulkner, 2016; 2018a; 2018b; 2020a; 2020b; Ohito & Nyachae, 2018; Prendergast, 2015) represents a significant piece of this project: how breath, pauses, slivers of silence(s), and slow pacing surfaced during teachers candidates’s disclosures of violence while discussing their learning about the pedagogical potential of Tarana Burke’s MeToo movement, centering sexual assault narratives in the English literature classroom, and resisting rape culture(s). Because participants’ testimonies of diverse trauma experiences demanded poetry of witness (Davidson, 2003), poetic inquiry allowed for attendance to these offerings through the composition of visual ‘silence poems’ that re-transcribe the disclosures by capturing nonverbal moments: gaps, pauses, trailings off, etc. With the aim of thinking ahead to how secondary English teachers might cultivate radical classroom communities prepared to cultivate radical solidarity as resistance to patriarchal violence, this paper explores how poetic inquiry might especially offer a significant methodological entrypoint for antirape research.